Genome-wide identification, expression pattern and genetic variation analysis of SWEET gene family in barley reveal the artificial selection of HvSWEET1a during domestication and improvement - Yue, Wenhao; Cai, Kangfeng; Xia, Xue; Liu, Lei; Wang, Junmei (Frontiers in Plant Science, 2023)
SWEET (Sugars Will Eventually be Exported Transporter) proteins, an essential class of sugar transporters, are involved in vital biological processes of plant growth and development. To date, systematical analysis of SWEET family in barley (Hordeum vulgare) has not been reported. In this study, we genome-wide identified 23 HvSWEET genes in barley, which were further clustered into four clades by phylogenetic tree. The members belonging to the same clade showed relatively similar gene structures and conserved protein motifs. Synteny analysis confirmed the tandem and segmental duplications among HvSWEET genes during evolution. Expression profile analysis demonstrated that the patterns of HvSWEET genes varied and the gene neofunctionalization occured after duplications. Yeast complementary assay and subcellular localization in tobacco leaves suggested that HvSWEE1a and HvSWEET4, highly expressed in seed aleurone and scutellum during germination, respectively, functioned as plasma membrane hexose sugar transporters. Furthermore, genetic variation detection indicated that HvSWEET1a was under artificial selection pressure during barley domestication and improvement. The obtained results facilitate our comprehensive understanding and further functional investigations of barley HvSWEET gene family, and also provide a potential candidate gene for de novo domestication breeding of barley.